2012
DOI: 10.1039/c1nr11282a
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stabilization of thin gold nanowires by surfactant-coating: a molecular dynamics study

Abstract: The thermal stabilization of thin gold nanowires with a diameter of about 2 nm by surfactants is investigated by means of classical molecular dynamics simulations. While the well-known melting point depression leads to a much lower melting of gold nanowires compared to bulk gold, coating the nanowires with surfactants can reverse this, given that the attractive interaction between surfactant molecules and gold atoms lies beyond a certain threshold. It is found that the melting process of coated nanowires is do… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Discrepancies of the order 20% between simulations and experiments are expected most notably because of differences in the grafting densities. The value of 3.8 ligands/nm 2 used in the simulations falls within the range of experimental estimates (2–8 ligands/nm 2 ), ,, which suffer from a large degree of currently unavoidable uncertainty . This uncertainty cannot be eliminated experimentally because there is no technique available that would provide the ligand density of individual wires and because it is unknown how broad the standard deviation of the density over many wires is.…”
Section: Resultsmentioning
confidence: 63%
“…Discrepancies of the order 20% between simulations and experiments are expected most notably because of differences in the grafting densities. The value of 3.8 ligands/nm 2 used in the simulations falls within the range of experimental estimates (2–8 ligands/nm 2 ), ,, which suffer from a large degree of currently unavoidable uncertainty . This uncertainty cannot be eliminated experimentally because there is no technique available that would provide the ligand density of individual wires and because it is unknown how broad the standard deviation of the density over many wires is.…”
Section: Resultsmentioning
confidence: 63%
“…22 The Universal force eld (UFF) 23 was adopted to perform this simulation. Previous studies 24,25 have shown that UFF provides reliable results for gold based systems. The cut-off radius was chosen to be 15.5 Å and a NVE ensemble was used.…”
Section: Methodsmentioning
confidence: 98%
“…The melting temperature of the AuUNW was predicted by classical MD simulations to increase with an increase in the attractive force between the surfactants. 35 The modulation of encapsulating shells made of polystyrene-blockpoly(acrylic acid) led to a transformation of straight AuUNWs to circular rings in colloidal solution (Figure 5d). 36 This method gave a structure resembling that of torsion springs (Figure 5e) in which elastic energy is stored.…”
Section: (D) Ac-hrtemmentioning
confidence: 99%